2010
DOI: 10.5194/aab-53-277-2010
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism of the kappa-casein gene in two Bosnian autochthonous cattle breeds

Abstract: Buša is an old endangered autochthonous breed of the western Balkan, especially Bosnia-Herzegovina, Kosovo and Albania. A related breed is Gatačko, derived from Buša × Tirolean Grey crossbreds. Fifteen purebred Buša cattle and thirteen Gatačko animals were genotyped for polymorphisms at the kappa-casein gene by a Polymerase Chain Reaction-Restriction Fragment Length Polymorphism (PCR-RFLP) essay. The alleles A, B and C were found and the allelic frequencies were 0.46 (A), 0.46 (B) and 0.08 (C) in Buša cattle a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 8 publications
2
7
0
Order By: Relevance
“…Many other authors (Taha and Punan, 1993, Dogru and Ozdemir, 2009, Dokso et al, 2014, Djedović et al, 2015 found that the frequency of the AB genotype in the Brown Swiss breed was higher compared to other genotypes, while Potočnik (2015) determined a higher share of BB genotypes compared to AA and AB in this breed. The higher frequency of BB genotype in Jersey cattle (0.772) with absent of opposite AA genotype is reported by Ren et al, 2011 Ho: observed heterozygotes, He: expected heterozygotes on the basis of Hardy-Weinberg, χ2 =chi-square value Similar to our research, Djedović et al (2015), Maletić et al (2016), Brka et al (2010) also obtained that heterozygote genotype of κ-casein (AB) was dominant in Busha breed. Only in the research of Ivanković et al (2011) determined dominance of BB homozygote.…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…Many other authors (Taha and Punan, 1993, Dogru and Ozdemir, 2009, Dokso et al, 2014, Djedović et al, 2015 found that the frequency of the AB genotype in the Brown Swiss breed was higher compared to other genotypes, while Potočnik (2015) determined a higher share of BB genotypes compared to AA and AB in this breed. The higher frequency of BB genotype in Jersey cattle (0.772) with absent of opposite AA genotype is reported by Ren et al, 2011 Ho: observed heterozygotes, He: expected heterozygotes on the basis of Hardy-Weinberg, χ2 =chi-square value Similar to our research, Djedović et al (2015), Maletić et al (2016), Brka et al (2010) also obtained that heterozygote genotype of κ-casein (AB) was dominant in Busha breed. Only in the research of Ivanković et al (2011) determined dominance of BB homozygote.…”
Section: Resultssupporting
confidence: 87%
“…On the other side, the results of genotyping k-caseine of Czech Fleckvieh, Bulgarian Rhodopean Cattle, Shorthorn Rhodopean Cattle as old autchthonous breed (Kučerová et al, 2006 andHristov et al, 2012), as well as results for Gatačko cattle reared in Bosnia and Herzegovina (Brka et al, 2010) show strong domination of the AB genotype, as it obtained for Gray cattle breed in Montenegro. In regarding allele frequencies of κ-casein gene for all three investigated breeds, slightly higher frequencies of A allel than B allele were determined.…”
Section: Resultsmentioning
confidence: 66%
See 1 more Smart Citation
“…According to international practice and reference to (Brka et al 2010, Kulig et al 2010 about the naming of SSCP patterns, In P2 locus, different SSCP patterns were named GG, GA and AA genotypes. The alleles were named G and A, and GG, GA and AA genotypes were found in the three goat breeds.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, Ren et al (2013) revealed that the B allele was higher than the A allele. Many researchers from different countries reported that A allele was more dominant in milk protein genes at dairy cows than other allele (Djedovic et al 2015;Brka et al 2010).…”
Section: Genetic Variants Of Milk Protein Genesmentioning
confidence: 99%